Incidence, prevalence and mortality of autoimmune hepatitis in England 1997‐2015. A population‐based cohort study. (2nd May 2020) - Grønbæk, Lisbet; Otete, Harmony; Ban, Lu; Crooks, Colin; Card, Timothy; Jepsen, Peter; West, Joe
Abstract: Background & Aims: There are few population‐based studies of the incidence and mortality of autoimmune hepatitis. The burden of the disease and how it has changed over time have not been fully explored. We conducted a population‐based cohort study on the incidence and mortality of autoimmune hepatitis in England, 1997‐2015. Methods: From the Clinical Practice Research Datalink we included 882 patients diagnosed with autoimmune hepatitis in England, 1997‐2015. The patients were followed through 2015, and we calculated the sex‐ and age‐standardized incidence and prevalence of autoimmune hepatitis. We examined variation in incidence by sex, age, calendar year, geographical region and socioeconomic status, and incidence rate ratios were calculated with Poisson regression. We calculated all‐cause and cause‐specific mortality. Results: The overall standardized incidence rate of autoimmune hepatitis was 2.08 (95% confidence interval 1.94‐2.22) per 100, 000 population per year, higher in women, higher in older age and independent of region and socioeconomic status. From 1997 to 2015 the incidence doubled from 1.27 (95% confidence interval 0.51‐2.02) to 2.56 (95% confidence interval 1.79‐3.33) per 100, 000 population per year. The 10‐year cumulative all‐cause mortality was 31.9% (95% confidence interval 27.6‐36.5), and the 10‐year cumulative liver‐related mortality, including hepatocellular carcinoma was ~10.5%. Conclusions: This population‐based study showed that the incidence of autoimmune hepatitis doubled over an eighteen‐year period. The incidence was particularly high in older women and was similar across all regions of England and independent of socioeconomic status. Patients with autoimmune hepatitis had a high mortality.